The effect of tension stiffening in moment-curvature responses of prestressed concrete members. (15th April 2022) - Dong Lee, Ju
Highlights: The inverse-engineering approach is used to examine the effect of concrete tensile strength on prestressed concrete members. A simple concrete tensile stress–strain model is proposed from a parameter study. The effect of concrete tensile stiffening is more prominent for partially-prestressed beams than fully-prestressed concrete beams. The concrete tensile characteristics is negligible when a ratio of axial compressive pressure to concrete compressive strength exceeds 0.1. Abstract: Although tensile resistance of concrete is often neglected in calculating the nominal flexural capacity of a concrete member, it needs to be taken into account to accurately trace the deformation response of concrete members as it affects pre- and post-cracking behavior. To adequately address tensile resistance contributed by concrete in moment–curvature analysis, it is necessary to exploit a proper concrete tensile stress–strain model. While constitutive stress–strain models of reinforced concrete in tension have been studied by many researchers and well documented, those of prestressed concrete have gained relatively less attention. There are also conflicting results on how prestressing force affects concrete tension stiffening. This study fills the gap in existing studies and suggests an appropriate and simple model capturing the concrete tensile stress–strain relationship of prestressed concrete in a moment–curvature analysis. Based on an inverse-engineering approach using experimental test data and nonlinear analysis results, the effect of concrete tension stiffening varied by the level of prestressing force is investigated. The results show that concrete tensile properties hardly affect the force–deformation response of beams with high-level prestressing. Additionally, several parameters related to concrete tension stiffening are examined in the parameter study. By comparing predicted moment–curvature responses with test data, ideal values for considered parameters are obtained. Based on the parameter study, simple equations are proposed that are expressed in concrete compressive strength to simulate the concrete tensile stress–strain responses of partially prestressed members. The proposed equations are demonstrated using several prestressed beam tests found in previous studies.